Therapeutic Utility of Homoeopathic Medicines in Osteoarthritis: A Comprehensive Review (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
AbstractBackground: Osteoarthritis (OA) represents a chronic degenerative disorder of synovial joints leading to pain, stiffness, and restricted motion. Limitations of conventional pharmacotherapy and the chronic nature of OA have encouraged exploration of complementary systems such as homoeopathy for safer symptomatic control. Objectives: To comprehensively evaluate available clinical and experimental evidence regarding the therapeutic utility of homoeopathic medicines in OA, highlighting fifteen key remedies and their characteristic indications. Methods: A narrative review of fifty publications retrieved from PubMed, Scopus, AYUSH Portal, and homoeopathic journals (1999 – 2024) was conducted. Included studies comprised randomized controlled trials (RCTs), observational and mechanistic studies evaluating homoeopathic interventions in OA. Data were synthesized descriptively according to PRISMA-adapted methodology. Results: Across studies, individualized and complex homoeopathic prescriptions demonstrated meaningful improvement in pain, stiffness, and function. Remedies such as Rhus toxicodendron, Bryonia alba, Calcarea fluorica, and Sulphur were most frequently indicated. Mechanistic reports suggest modulation of inflammatory and oxidative pathways. Evidence quality remains limited by small samples and heterogeneity, yet safety outcomes were uniformly favorable. Conclusion: Homoeopathy may serve as an effective and well-tolerated adjunct in OA management. Further large-scale, well-designed trials with standardized outcome measures are essential to establish efficacy and clarify mechanisms.